Stereo vision with laser diode distance measurement - Mahammed, Manaf A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
An efficient technique is used to measure the distance of a target from the camera. A laser diode emitter is used to illuminate the desired portion of the target with bright laser spot and a 3D web camera is used to image the target. Image processing together with stereo vsion basic equations were used to calculate the distance from the measuring of disparity between the two images of the bright laser spot on the target. The results were compared with tests made using digital laser range finder and showed good agreement. The percentage error ranged from 0.025 % to 1.757 %.
Keywords: Laser emitter stereo 3D webcam distance disparity